IMPLIKASI LARANGAN PERNIKAHAN TUNAGRAHITA BERAT PERSPEKTIF MAQOSID SHARIAH JASER AUDA - Hawa’ Hidayatul Hikmiyah; Ahmad Faisol; St Sariroh (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
Everyone has right to get married, unlike the case with people with severe mental retardation. There are adverse effects if mental retardation still gets the legality to get married. This marriage ban is categorized as severe mental retardation shich cant be done at all, and all work must be replaced by someone els. Because of the prohibition of marriage for people with intellectual disabilities that is feared to other people, it is difficult to create a marriage destination and it is feared that it will have an impact on children who will be born like their parents. If seen in terms of its benefits, the existence of the ban becomes a benefit. The application of system theory as an approach in Islamic law, there are six system features used by Jasser Auda as a knife of analysis namely cognitive nature, wholeness, openness, interleted hierarchy, multi dimentionality and pusposefullness. By using theory of Maqo>sid Shari>‘ah Jasser Auda it will be seen that the prohibition of marriage for person with severe mental retardation is policy that is not merely to protect the rights of individuals but protect the rights of the general public, taking into account the puspose, function, maslahah and mudarat.",